Data describing the eco-physiological responses of twenty-four sunflower genotypes to water deficit - Nicolas Blanchet; Pierre Casadebaig; Philippe Debaeke; Harold Duruflé; Louise Gody; Florie Gosseau; Nicolas B. Langlade; Pierre Maury (Data in Brief, 2018)
This article presents experimental data describing the physiology and morphology of sunflower plants subjected to water deficit. Twenty-four sunflower genotypes were selected to represent genetic diversity within cultivated sunflower and included both inbred lines and their hybrids.Drought stress was applied to plants in pots at the vegetative stage using the high-throughput phenotyping platform Heliaphen at INRA Toulouse (France). Here, we provide data including specific leaf area, osmotic potential and adjustment, carbon isotope discrimination, leaf transpiration, plant architecture: plant height, leaf number, stem diameter. We also provide leaf areas of individual organs through time and growth rate during the stress period, environmental data such as temperatures, wind and radiation during the experiment. These data differentiate both treatment and the different genotypes and constitute a valuable resource to the community to study adaptation of crops to drought and the physiological basis of heterosis. It is available on the following repository: https://doi.org/10.25794/phenotype/er6lPW7V Keywords: Helianthus, Abiotic stress, Phenotyping platform, Drought stress